Model based psychoeducational on the neocortex brain and its influence on the personality of university students - Ostos-Miraval, Reynaldo M. (2019)
The objective of the study is to demonstrate the influence of the model-based psychoeducational cerebral neocórtex as informational social-psychological system that improve the level of personality adjustment and interpersonal values in UNHEVAL university students.Methods: An experimental study, non-probability sampling with two groups of 25 students, were used inventory of personality fit and reliability of r = 0.96, the questionnaire test retest reliability interpersonal values vary between 0.71 and 0.86 Kuder-Richardson  adapted to Peruvian scales. Statistical Mc Nemar test, significance level of 0.05 and contingency table 2 x 2 and 2 frequency inputs, designs before and after, were observed and no improvement, improvement achieved by the experimental and control groups.Results: Post-test, the improvement was achieved in the inventory adjustment in the areas of personality: emotional (48%) excellent (40%) good, achieving an improvement (88%), who have control of their emotions, conflicts tolerance, free from fear, Health (52%) good, (44%) and regular (4%) with excellent and improved (56%). Social (80%) and aggressive (8%) very aggressive, improve (88%), home (40%) good (60%) regularly, improves the qualities of the father-child relationship and brotherly. Scales of interpersonal values support the high level (56%), dealing with understanding, kindness, affection, support and encouragement of others; compliance (52%), attitudes of respect, acceptance of social norms and rules, to the socially correct; recognition (76%), with attitudes of admiration, be considered important person and get recognition from others; independence (48%), free to make decisions for yourself, act for their own judgment; benevolence (60 %), sense of mission and solidarity, leadership (84%). Conclusions: The model applied based psychoeducational cerebral neocórtex as informational social-psychological system, showed significant improvement in the quality levels of personality adjustment and interpersonal values.